VacStent as a novel therapeutic approach for esophageal perforations and anastomotic leaks– a systematic review of the literature - Kehagias, Dimitrios; Abogabal, Sameh; Lampropoulos, Charalampos; Haider, Muhammad Ijlal; Kehagias, Ioannis; Jain, Prashant; Wong, Vincent (BMC surgery, 2025)
Background Perforation and anastomotic leak (AL) of the esophagus remain a dreaded complication for surgeons, endoscopists and patients. The VacStent is a novel endoscopic device, combining the benefits of a self-expandable metallic stent (SEMS) and endoscopic vacuum therapy (EVT). This systematic review aims to investigate the efficacy and clinical outcomes associated with the use of the VacStent. Methods A systematic literature review was conducted in PubMed and Google Scholar electronic databases using keywords and Medical Subject Headings terms. Peer-reviewed studies in English language that reported the use of VacStent for transmural defects of any cause of the esophagus and gastroesophageal junction (GEJ) were included. Data regarding technical details of the VacStent, outcomes, and complications were extracted and presented in a narrative synthesis. Clinical success was defined as closure of the defect without requiring further intervention. Results Of the 153 articles identified after searching, nine studies were deemed eligible and included in the final analysis. The methodological quality of the included studies was generally moderate. Sixty-five patients underwent VacStent treatment for the following indications: AL (70%), Boerhaave syndrome (10%), iatrogenic perforation (10%), and other causes (10%). The mean interval between VacStent changes was 5.3 (2–8) days. Prior endoscopic interventions, including SEMS, clips, and EVT, had been performed in 25 patients (38%). The mean duration of VacStent therapy was 8.8 ± 8.3 days. On average, each patient received between one and three VacStents. Technical success was achieved in all 65 cases (100%), while clinical success was observed in 50 patients (77%). Approximately 70% of patients were able to tolerate a liquid diet during treatment, and no major complications were reported. Conclusions The VacStent appears as a promising tool, integrating the benefits of both EVT and SEMS, while allowing oral intake. The included studies present preliminary data, warranting cautious interpretation. Further evidence is required to delineate the clinical utility and appropriate indications for VacStent therapy. Trial Registration PROSPERO database (UIN: CRD420251012718).